Identifying potential pharmacological targets and molecular pathways of Meliae cortex for COVID-19 therapy - Khan, Shakeel Ahmad; Lee, Terence Kin Wah (Frontiers in Immunology, 2023)
Coronavirus disease-19 (COVID-19), caused by SARS-CoV-2, has contributed to a significant increase in mortality. Proinflammatory cytokine-mediated cytokines release syndrome (CRS) contributes significantly to COVID-19. Meliae cortex has been reported for its several ethnomedical applications in the Chinese Pharmacopoeia. In combination with other TCM, the Meliae cortex suppresses coronavirus. Due to its phytoconstituents and anti-inflammatory capabilities, we postulated that the Meliae cortex could be a potential therapeutic for treating COVID-19. The active phytonutrients, molecular targets, and pathways of the Meliae cortex have not been explored yet for COVID-19 therapy. We performed network pharmacology analysis to determine the active phytoconstituents, molecular targets, and pathways of the Meliae cortex for COVID-19 treatment. Phytoconstituents of the Meliae cortex and their targets from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) and SwissTargetPrediction website tool, respectively, were retrieved. COVID-19-related targets were recovered from the GeneCards. Using the DAVID tool, gene ontology (GO) and KEGG pathway enrichment analysis were performed on the intersection gene targets. Using the Cytoscape software, the PPI and MCODE analyses were carried out on the intersection gene targets. Molecular docking was performed with AutoDock Vina. 15 active phytonutrients and 451 their potential gene targets, 1745 COVID-19-related gene targets, and 104 potential anti-COVID-19 prime targets, 41 potential anti-COVID-19 core targets were determined. The 10 anti-COVID-19 core targets (AKT1, TNF, HSP90AA1, IL6, mTOR, EGFR, CASP3, HIF1A, MAPK3, and MAPK1), three molecular pathways (the PI3K-Akt signaling pathway, the HIF-1 signaling pathway, and the pathways in cancer) and three active phytonutrients (4,8-dimethoxy-1-vinyl-beta-carboline, Trichilinin D, and Nimbolin B) were identified as molecular targets, molecular pathways, and key active phytonutrients of the Meliae cortex, respectively that significantly contribute to alleviating COVID-19. Molecular docking analysis further corroborated that three Meliae cortex’s key active phytonutrients may ameliorate COVID-19 disease by modulating identified targets. Hence, this research offers a solid theoretic foundation for the future development of anti-COVID-19 therapeutics based on the phytonutrients of the Meliae cortex.